The Ancient Egyptian Origin of a Transcultural Trope, across Classical, Islamic, and Jewish Traditions: The First Attestation of the Crocodile Bird in Egyptian, or Why Herodotus Is Not a Liar (with the First Edition of P. Vienna D 6104) - Prada, Luigi (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The article studies the trope of the crocodile bird in its evolution from antiquity to the present day. The story tells of the mutualistic behaviour between the Nile crocodile and an Egyptian bird, typically known as the trochilus . The trope has a complex history: primarily known from classical writers, it spread in fact to Jewish and Islamic traditions, too. The story is universally thought to be an invention of Herodotus. But a demotic papyrus, here published for the first time, proves that the trope of the crocodile bird has its true origin in ancient Egyptian culture.